Weld morphology and grain growth characteristics of driven moving arc hollow stud welding - Deku Zhang; Xinkai Zhu; Hongyu Yin; Kehong Wang; Guangjun Zhang (Journal of Materials Research and Technology, 2023)
During the welding process of hollow studs, several issues can arise, including arc deflection, local non-fusion, welding pores, and cracks. In response to these challenges, a rotating magnetic field device has been developed to enhance the welding arc movement, which in turn improves the joint formation and weld grain growth behavior. According to the results, the arc moves in a periodic manner along the end face of the stud when exposed to a rotating magnetic field, due to the application of the Lorentz force. This leads to an enhanced uniformity of the melting process, a reduction in the occurrence of localized un-fusion and porosity defects, and an overall improvement in the quality of the weld morphology. Under the electromagnetic stirring effect, the undercooling of the molten pool changes and the microalloying elements in high-strength steel diffuse into the welded joint. The microstructure of the welded joint area is transformed into martensite, lower bainite, and needle-like ferrite. Under the action of a rotating magnetic field, the coarse grain in the welded joint is broken and the size is refined from 2.91 μm to 1.48 μm. The number of high-angle grain boundaries increases while the number of low-angle grain boundaries decreases. The shear strength of the joint is improved from 227 MPa to 315 MPa.